UX Analysis and UI Development of iOS-Based Bali Calendar Application with Double Diamond Method - Darma Paramartha, I Gusti Ngurah; Ariesta, Ni Luh Wina Sinta; Gama, Adie Wahyudi Oktavia; Prathama, Gede Humaswara (Jurnal Info Sains : Informatika dan Sains, 2024)
The Bali Calendar iOS application is designed to make it easier for users to access information related to the traditional Balinese calendar, such as determining rahina. However, the current features of the application are not yet optimal. Based on reviews on the App Store, many users have suggested adding features such as searching for dewasa ayu, otonan, Tri Sandhya alarms and chants, panca sembah, and daily prayers. The purpose of this research is to understand user needs and design the interface of the Bali Calendar iOS application based on user feedback to improve user satisfaction. The research method used is the Double Diamond approach, which consists of two phases: the research phase and the design phase. Each phase comprises two stages. The research phase includes the discover and define stages, while the design phase encompasses the develop and deliver stages. The outcome of this research is a prototype design for the Bali Calendar iOS application, which will be tested by users. The prototype design is evaluated using concept testing to assess the concept and usability testing to evaluate the prototype design. The results of the usability testing achieved high scores, indicating that the design is satisfactory and effectively meets user needs.